2008
DOI: 10.1021/jm8008713
|View full text |Cite
|
Sign up to set email alerts
|

Novel d-Xylose Derivatives Stimulate Muscle Glucose Uptake by Activating AMP-Activated Protein Kinase α

Abstract: Type 2 diabetes mellitus has reached epidemic proportions; therefore, the search for novel antihyperglycemic drugs is intense. We have discovered that D-xylose increases the rate of glucose transport in a non-insulin-dependent manner in rat and human myotubes in vitro. Due to the unfavorable pharmacokinetic properties of D-xylose we aimed at synthesizing active derivatives with improved parameters. Quantitative structure-activity relationship analysis identified critical hydroxyl groups in D-xylose. These data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Dozens of molecules that activate AMPK, directly or indirectly, were synthesized or extracted from plants. In the course of our work, we found that the pentose D-xylose augmented the rate of glucose transport in L6 and human myotubes under high glucose conditions by activating AMPK [132]. Because this effect of D-xylose was obtained at very high concentrations (10-20 mM), we synthesized more potent lipophilic derivatives of D-xylose.…”
Section: D-xylose and Lipophilic D-xylose Derivativesmentioning
confidence: 93%
See 1 more Smart Citation
“…Dozens of molecules that activate AMPK, directly or indirectly, were synthesized or extracted from plants. In the course of our work, we found that the pentose D-xylose augmented the rate of glucose transport in L6 and human myotubes under high glucose conditions by activating AMPK [132]. Because this effect of D-xylose was obtained at very high concentrations (10-20 mM), we synthesized more potent lipophilic derivatives of D-xylose.…”
Section: D-xylose and Lipophilic D-xylose Derivativesmentioning
confidence: 93%
“…Representative blot and a summary of n = 3 (* p<0.05) in comparison with the respective controls. Reproduced with permission from [132]. gluconeogenesis in the liver by activating AMPK [98].…”
Section: Metformin and Thiazolidinedionesmentioning
confidence: 99%
“…More potent derivatives of D-xylose, such as 2,4;3,5-dibenzylidene-D-xylose-diethyldithioacetal, 2,4-benzylidene-D-xylose-diethyl-dithioacetal, and 2,4-benzylidene-D-xylose-3-O-methyl-diethyl-dithioacetal, were synthesized that showed signifi cant stimulation of glucose uptake in myotubes at concentrations ranging from 5 to 100 M. This effect occurs via AMPK activation through AMPK phosphorylation at Thr-172 and inhibited by the AMPK inhibitor Compound C, suggesting involvement of AMPK activation. Some of these compounds reduced blood glucose levels in the genetically diabetic KKA y mice ( 268 ) and show potential as antihyperglycemic compounds.…”
Section: D-xylose and Lipophilic D-xylose Derivativesmentioning
confidence: 99%
“…Epigallocatechin gallate [71] Stimulates ROS generation, which in turn activates AMPK 65 Genistein [72] 51…”
Section: Ampk Activator and Diabetic Ulcer Animal Studymentioning
confidence: 99%